- Analisis Filsafat Absurdisme dan Harapan Kristen pada Kasus Penutupan Gereja di Indonesia - Manalu, Musdodi (STFT Jakarta, Indonesia, 2025)
Religious intolerance against Christians in Indonesia — ranging from prohibitions on worship to the destruction of church buildings — raises urgent existential questions about how recurring suffering can be understood and responded to theologically. While the theology of the cross offers a framework for making sense of such suffering, its dialogue with absurdist philosophy, which confronts suffering directly and without recourse to transcendent hope, remains underexplored in Indonesian contextual theology. This article aims to analyze the points of convergence and divergence between Albert Camus’s absurdism, particularly the figure of Sisyphus, and the theology of the suffering of Christ’s cross as a reflective framework for oppressed Christians. Drawing on a library research method and philosophical-theological discourse analysis applied to Camus’s writings, theological literature on the suffering of Christ, and documentation of intolerance cases, the article identifies three points of both convergence and divergence: both acknowledge suffering as a recurring and unavoidable burden; both require active consciousness in bearing it; yet they differ fundamentally in their ultimate orientation — Sisyphus chooses revolt without transcendent hope, while Christian faith endures in the hope of salvation. Rather than cancelling each other out, absurdism and the theology of the cross function as a dialogical mirror that sharpens theological understanding of suffering while offering concrete ethical and existential resources for oppressed Christian communities in Indonesia.